The ph of drinking water alters the metabolic and neurobehavioral response of rats exposed to vitamin d3 or prednisolone - Abdulrazaq, Omar Medhat; Zuher AL-Abdaly, Yamama (Vojenské zdravotnické listy, 2023)
Background: The degree of blood pH affects the fundamental function of vitamin D, which is to maintain calcium and phosphorus as well as many other biochemical, neurological, and behavioural activities the difference in blood pH impacts the levels of calcium and vitamin D in the blood, and it is also in charge of ensuring that calcium levels are suitable and constant.Objective: that blood pH affects the basic function of calcium and phosphorus and vitamin D, the difference in pH affects calcium and vitamin D levels in the blood and is also responsible for keeping calcium levels appropriate and stable.Methods: 7 groups composed of 35 mature female rats were divided at random.Results: After 24 hours, none of the animals died. While stress activity increased with alkaline water, vitamin D3 and calcium levels increased in the acid water group while their concentration decreased with prednisolone, while calcium levels did not change in the alkaline water group. The animals in the two groups of vitamin D3 and acidified water with or without prednisolone moved less in the open field. Along with increased oxidative stress, vitamin D3 with acid water also inhibited cholinesterase activity. The lipid profile in the blood is impacted by the vitamin D3 group in both acidic and alkaline water.Conclusion: Prednisolone reduces serum levels of vitamin D3. And that acidic water directly affects the toxicity of vitamin D3, while alkaline water significantly reduces toxicity.
Keywords: Neurologic Manifestations; dospělí; Statistics as Topic; Female; Prednisolone; Blood Chemical Analysis; statistika jako téma; Hydrogen-Ion Concentration; prednisolon; Adult; ženské pohlaví; pitná voda; biochemická analýza krve; vápník; Models, Animal; Cholecalciferol; Calcium; cholekalciferol; Drinking Water; krysa rodu Rattus; neurologické manifestace; koncentrace vodíkových iontů; Rats; modely u zvířat